Does levonorgestrel emergency contraceptive have a post-fertilization effect? A review of its mechanism of action. (2nd January 2016) - Peck, Rebecca; Rella, Walter; Tudela, Julio; Aznar, Justo; Mozzanega, Bruno
Abstract : Background : Recent studies have identified that levonorgestrel administered orally in emergency contraception (LNG-EC) is only efficacious when taken before ovulation. However, the drug does not consistently prevent follicular rupture or impair sperm function. Objective : The present systematic review is performed to analyze and more precisely define the extent to which pre-fertilization mechanisms of action may explain the drug's efficacy in pregnancy avoidance. We also examine the available evidence to determine if pre-ovulatory drug administration may be associated with post-fertilization effects. Conclusion : The mechanism of action of LNG-EC is reviewed. The drug has no ability to alter sperm function at doses used in vivo and has limited ability to suppress ovulation. Our analysis estimates that the drug's ovulatory inhibition potential could prevent less than 15 percent of potential conceptions, thus making a pre-fertilization mechanism of action significantly less likely than previously thought. Luteal effects (such as decreased progesterone, altered glycodelin levels, and shortened luteal phase) present in the literature may suggest a pre-ovulatory induced post-fertilization drug effect. Lay Summary: Plan B is the most widely used emergency contraceptive available. It is important for patients and physicians to clearly understand the drug's mechanism of action (MOA). The drug was originally thought to work by preventing fertilization. Recent research has cast doubt on this. Our review of the research suggests that it could act in a pre-fertilization capacity, and we estimate that it could prevent ovulation in only 15 percent or less of cases. The drug has no ability to alter sperm function and limited ability to suppress ovulation. Further, data suggest that when administered pre-ovulation, it may have a post-fertilization MOA.